The distributional impact of public services when needs differ - Rolf Aaberge; Manudeep Bhuller; Audun Langørgen; Magne Mogstad (Statistics Norway, Research Department, 2010)
Despite a broad consensus on the need to take into account the value of public services in distributional analysis, there is little reliable evidence on how the inclusion of such non-cash income actually affects poverty and inequality estimates. In particular, the equivalence scales applied to cash income are not necessarily appropriate when including non-cash income, because the receipt of public services is likely to be associated with particular needs. In this paper, we propose a theory-based framework designed to provide a coherent evaluation of the distributional impact of local public services. The valuation of public services, identification of target groups, allocation of expenditures to target groups, and adjustment for differences in needs are derived from a model of local government spending behaviour. Using Norwegian data from municipal accounts and administrative registers we find that the inclusion of non-cash income reduces income inequality by about 15 percent and poverty rates by almost one-third. However, adjusting for differences in needs for public services across population subgroups offsets about half the inequality reduction and some of the poverty decrease.
Keywords: D31; H72; I30; 330; Income distribution; poverty; public services; non-cash income; needs adjustment; equivalence scales